2015
DOI: 10.1088/1748-3190/10/5/055006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bladder wall thickness on miniature pneumatic artificial muscle performance

Abstract: Pneumatic artificial muscles (PAMs) are actuators known for their high power to weight ratio, natural compliance and light weight. Due to these advantages, PAMs have been used for orthotic devices and robotic limbs. Small scale PAMs have the same advantages, as well as requiring greatly reduced volumes with potential application to prostheses and small scale robotics. The bladder of a PAM affects common actuator performance metrics, specifically: blocked force, free contraction, hysteresis, and dead-band press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
(40 reference statements)
0
35
0
Order By: Relevance
“…Tiwari et al (2012) and Meller et al (2014) included work comparing hydraulic and pneumatic actuation—the results indicate that while pneumatics are cleaner and often have a simpler fluid circuit, the compressibility of air causes pneumatic FAMs to be less efficient than their hydraulic counterparts. More recent studies have found more in-depth, predictive models of FAM output force and stroke during static and dynamic conditions (Ball and Garcia, 2016; Pillsbury et al, 2015; Sangian et al, 2015; Tondu, 2018). There have also been studies of how FAM design parameters impact the efficiency of an entire electro-hydraulic system in a self-contained mobile robot (Chapman et al, 2017) as well as multiple other applications of FAMs in robotic and rehabilitation applications (do Nascimento et al, 2008; Gordon et al, 2006; Pack et al, 1997; Tondu and Lopez, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tiwari et al (2012) and Meller et al (2014) included work comparing hydraulic and pneumatic actuation—the results indicate that while pneumatics are cleaner and often have a simpler fluid circuit, the compressibility of air causes pneumatic FAMs to be less efficient than their hydraulic counterparts. More recent studies have found more in-depth, predictive models of FAM output force and stroke during static and dynamic conditions (Ball and Garcia, 2016; Pillsbury et al, 2015; Sangian et al, 2015; Tondu, 2018). There have also been studies of how FAM design parameters impact the efficiency of an entire electro-hydraulic system in a self-contained mobile robot (Chapman et al, 2017) as well as multiple other applications of FAMs in robotic and rehabilitation applications (do Nascimento et al, 2008; Gordon et al, 2006; Pack et al, 1997; Tondu and Lopez, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This is regulated by the central nervous system by the motor neurons and their associated axons (Henneman et al, 1965b). An analogous behavior can be created in FAMs; those with thicker or stiffer elastomeric bladder materials tend to require larger applied pressures before output force or significant contraction are generated (Pillsbury et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the improved model and the measured data shown that the improved model can predict muscle static response more accurately. Pillsbury et al [19] fabricated and tested several PAMs with bladder thickness that varied between 0.397 mm and 0.794 mm. They verified that contraction force and free contraction both decrease with increasing bladder thickness.…”
mentioning
confidence: 99%